Answer:
1240 students
Step-by-step explanation:
not sure but I'm pretty sure its right.
Distribute
remember a(b+c)=ab+ac
8(y+4)=8(y)+8(4)=8y+32
8y+32=7y+38
minus 7y both sides
y+32=38
mius 32 oth sides
y=6
The equation would be: (x + 6)^2 + (y + 3)^2 = 25
This equation will produce a circle. If you add the numbers inside the parenthesis to be squared, you can center of the circle. Thus, translating the shape.
Answer:
26
Step-by-step explanation:
24²+10²=x²
676=x²
x=√676
x=26
Pythagorean theorem
Answer:
Option a
Step-by-step explanation:
Lets verify
RHS
![\\ \rm\longmapsto x(x^2-3)](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Clongmapsto%20x%28x%5E2-3%29)
- Use distributive law
- a(b-c)=ab-bc
![\\ \rm\longmapsto x(x^2)-3x](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Clongmapsto%20x%28x%5E2%29-3x)
![\\ \rm\longmapsto x^3-3x](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Clongmapsto%20x%5E3-3x)
![\\ \rm\longmapsto LHS](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Clongmapsto%20LHS)
Hence verifed